Research on effect of Ca-treatment on Non-oriented Silicon-Steel - kong wei; Daqiang Cang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Tundish nozzle (submerged entry nozzle) clogging has always happened during a continuous casting process (or CC for short) for a non-oriented silicon steel. To solve the problem, the paper studied a flow rate through the tundish nozzles, a node attached to the tundish nozzles and the effect of Ca-treatment on it. The results showed that: When the tundish nozzles are clogged seriously, the casting speed has to decrease below the target casting speed; And tundish nozzle clogging can be predicted is by comparing the actual value and the theoretical one of a casting speed. Al2O3 and its composite inclusions were the reason that caused the tundish nozzle clogging; And Ca-treatment can solve tundish nozzle clogging during a CC process of the silicon steel both theoretically and practically. Furthermore, the effect of Ca-treatment on the magnetic properties of the steel was analyzed. The results showed that: The core loss and the magnetic induction of the silicon steel decreased by using Ca-treatment, which generated more dissolved Aluminum; And Ca-treatment generated more harmful textures, which reduced the magnetic induction.